2013
DOI: 10.1049/iet-map.2013.0076
|View full text |Cite
|
Sign up to set email alerts
|

Inkjet printed dipole antennas on textiles for wearable communications

Abstract: This paper presents an inkjet printed textile antenna realised using a novel fabrication methodology. Conventionally, it is very difficult to inkjet print onto textiles due to surface roughness. This paper demonstrates how this can be overcome by developing an interface coated layer which bonds to a standard polyester cotton fabric, creating a smooth surface. A planar dipole antenna has been fabricated, simulated and measured. This paper includes DC resistance, RF reflection coefficient results and antenna rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
84
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 118 publications
(87 citation statements)
references
References 36 publications
2
84
0
1
Order By: Relevance
“…The majority of papers in the literature do not include efficiency values for inkjet printed antennas as these are typically low. A more comprehensive review of inkjet printing can be found in [17] which demonstrated that two inkjet conducting layers with the interface layer gave superior performance to 5 layers without.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of papers in the literature do not include efficiency values for inkjet printed antennas as these are typically low. A more comprehensive review of inkjet printing can be found in [17] which demonstrated that two inkjet conducting layers with the interface layer gave superior performance to 5 layers without.…”
Section: Introductionmentioning
confidence: 99%
“…Quite recently, embroidered patch antennas [46] gained in popularity, thanks to the availability of low-cost automatic embroidery machines that operate with conductive yarns, These machines enable the study of different embroidery patterns for antenna and ground plane, which is very useful in the context of RFID tags [47]. Finally, additive techniques may be applied, such as screen or inkjet printing, to define antenna, reflector and ground-plane patterns on the garment [32], [49]- [51]. The first screen-printed textile antennas appeared in 2008 [48].…”
Section: B Materials and Technologiesmentioning
confidence: 99%
“…In addition, washable screenprinted textile antennas for 2.45 GHz ISM band [32][51] and for UHF-RFID tags [34] were introduced in 2012. In 2013, it was demonstrated that textile antennas may be inkjet-printed, provided a screen-printed interface layer is first applied to reduce the surface roughness of the textile substrate [49] [50]. A particularly interesting recent fabrication technique, first introduced in 2012 [53], consists of applying substrate waveguide technology to create cavities in textile substrate by means of rows of eyelets (Figure 4) or by embroidery.…”
Section: B Materials and Technologiesmentioning
confidence: 99%
“…This research not only has an important scientific significance, but also has an practical value in the field of radar absorbing material, communication window, fabric antenna, flexible functional clothing and so on [11,12]. At present, domestic and foreign researchers have studied 2D FSF by screen printing [13,14], weaving [15], weft knitting [16,17], embroidery [18,19], selective chemical plating [20], ink-jet printing [21] or other textile processing.…”
Section: Introductionmentioning
confidence: 99%